PENGARUH LEMBAR KERJA BERBASIS DIFFIT ARTIFICIAL INTELLIGENCE TERHADAP KETERLIBATAN SISWA DALAM PEMBELAJARAN AGAMA ISLAM KELAS VII DI SMP NEGERI 7 SAMBAS TAHUN AJARAN 2024-2025 - Hadisa Nadia; Purniadi Putra; Parni Parni (ADIBA : JOURNAL OF EDUCATION, 2025)
This study aims to examine the effect of using artificial intelligence (AI)-based worksheets on student engagement in Islamic Religious Education (PAI) learning among seventh-grade students at SMP Negeri 7 Sambas. The research employed a quantitative approach with a quasi-experimental design, involving two classes: one experimental class using AI-based worksheets and one control class using conventional methods. The research instruments consisted of pre-test, post-test, observation, and a student engagement questionnaire, analyzed using t-tests and PLS-SEM. The findings revealed that before the intervention, student engagement levels were relatively low in both the experimental class (average score 62.8) and the control class (57.7). After the implementation of AI-based worksheets, student engagement in the experimental class increased significantly to an average score of 86.8, while the control class only reached 61.63. The t-test results indicated a significant difference between the two groups. Moreover, the PLS-SEM analysis confirmed the validity and reliability of the instruments and reinforced the positive effect of AI-based worksheets on student engagement. In conclusion, AI-based Diffit worksheets significantly enhanced students’ cognitive, affective, and psychomotor engagement in PAI learning. These findings suggest that integrating AI technology into religious education can serve as an effective strategy to foster active student participation in the digital era.